Vigilancia tecnológica de vehículos eléctricos y tecnologías periféricas en Colombia (2016)
This article describes a study on Surveillance Technology (VT) and Forecast applied to Electric Vehicles (EVs) and Peripheral technologies in Colombia. We identify technologies associated with EVs, which are analyzed at investigative and market levels allowing us to obtain tendencies regarding research and maturation of technologies in EVs; we also identify the most representative technologies for research development. The study of Surveillance Technology allows the identification of the importance of intelligent networks to the growth in use of electric vehicles as they allow us to optimize the energy management of the distribution network and control the impact on the electric network. Additionally, the potential electronics present in the recharging systems of EVs, supply drives and electric motor control, added to interconnected intelligent systems, are relevant to research and the technological development of EVs.